Validating the process for labeling Moodle activities according to Complex thinking theory - Oliveira, Gustavo P.; Fernandes, Marcia A.; Maissiat, Jaqueline (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
This study proposes and evaluates Moodle activities labeling according to the abilities related to the subject’s cognitive aspect, punctuated by the complex thinking theory. The labeling’s qualitative character consisted of 30 educators’ responses from a federal institution to a form, aiming to relate skills to activities. The conceptual analysis of the labeling process and the grouping of responses from the form composed the quantitative labeling factor, resulting in reliable labeling. Comparisons between this labeling and a previous one highlighted similarities and discoveries. This labeling makes it possible to identify significant student characteristics presented by this theory and, consequently, the use of pedagogical activities that explore and expand higher-order skills.